Differences in MPV (Mean Platelet Volume) / Lymphocytes Ratio In Chronic Hepatitis B with and without Cirrhosis Hepatic - Elsha, Elsha Sinulingga; Siregar, Jelita; Sungkar, Taufik (Journal of Society Medicine, 2024)
Introduction: The MPV/Lymphocyte Ratio is a simple inflammatory parameter that can be obtained from a complete blood count. Hepatitis patients with liver cirrhosis have a higher MPV causing thrombopoietin to decrease so that the platelet count decreases. The inflammatory response can cause a decrease in the number of lymphocytes and is closely related to a poor prognosis in patients with hepatitis B virus. This study aims to examine the differences in the MPV/Lymphocyte ratio in chronic hepatitis B patients with and without liver cirrhosis. Methods: The samples for this study was chronic hepatitis B patients with and without liver cirrhosis who met he inclusion criteria. The research was carried out by taking blood samples from 94 patients treated in the internal medicine treatment room and Gastroenterohepatology polyclinic at Adam Malik Hospital, Medan. Samples were examined for MPV, absolute lymphocytes, then the MPV/lymphocyte ratio was calculated. Results: The total number of subjects in this study was 94 and there were 62 men and 32 women. The results of the analysis showed that there was a significant difference between the cirrhotic and non-cirrhotic groups (p = 0.001). Conclusion: There was a significant difference in the ratio of MPV/lymphocytes in the group of hepatitis B subjects with cirrhosis and in the group of hepatitis B subjects without liver cirrhosis. (p = 0.001).